Friction stir welding process improvement through coupling an optimization procedure and three-dimensional transient heat transfer numerical analysis - Boukraa, Moustafa; Lebaal, Nadhir; Mataoui, Amina; Settar, Abdelhakim; Aissani, Mouloud; Tala-Ighil, Nacer (Journal of manufacturing processes, 2018)
•The numerical model has shown a good correlation with experimental data.•The optimization of the maximum temperature during Friction Stir Welding.•The minimization of the Heat Affected Zone (HAZ) length.•The reduction of th nitial objective function e total welding energy.•The optimal parameters have given an ideal welding temperature in the workpiece. The present study deals with the improvement of the Friction Stir Welding process, through the prediction of the optimal operating conditions, necessary for welding typical Aluminum-Lithium alloy material AA2195-T8. An optimization strategy coupled with 3D transient heat transfer computation were used to improve the FSW process parameters such as welding velocity, tool rotation velocity, tool diameter and applied force. The optimization procedure is based on three criteria: the control of the maximum temperature during FSW; the minimization of the Heat Affected Zone (HAZ) length and finally the reduction of the total welding energy. The obtained optimal parameters have given an ideal welding temperature in the workpiece, thereby ensuring good welding quality, gain in energy consumption and decrease both the welding time and the HAZ length.